Role of immune response in Yersinia pestis infection - Amedeo Amedei; Elena Niccolai; Luigi Marino; Mario Milco D'Elios (Journal of Infection in Developing Countries)
Yersinia pestis (Y. Pestis) is an infamous pathogen causing plague pandemics throughout history and is a selected agent of bioterrorism threatening public health. Y. pestis was first isolated by Alexandre Yersin in 1894 in Hong Kong and in the years to follow from all continents. Plague is enzootic in different rodents and their fleas in Africa, North and South America, and Asia such as Middle/Far East and ex-USSR countries.